Transsexualism and Existentialism (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
This paper explores existential themes encountered in therapeutic practice with transsexual (trans) people. Drawing from her experience as a clinician within a large NHS clinic concerned with transgender care the author outlines the nexus of transsexualism with choice, freedom, authenticity, the existential 'givens', facticity and the making of a 'leap to faith'.
Keywords: Transsexual; trans; transvestite; transgender; authenticity; facticity; gender; givens.